Mushroom-Like EBG to Improve Patch Antenna Performance For C-Band Satellite Application - M. K. Abdulhameed; M. S. Mohamad Isa; Z. Zakaria; Mowafak K. Mohsin; Mothana L. Attiah (Institute of Advanced Engineering and Science, 2018)
In order to suppress the surface waves excitation that are caused by thick substrate in a patch antenna, a mushroom-like EBG (Electromagnetic Band Gap) structure is used. Such structures enhance its characteristics of gain, directivity, bandwidth and efficiency. Firstly, we determined frequency band gap characteristics of mushroom like EBG unit cell value by using CST software with 3mm (0.06λo) for covering 6 GHz. The periodic arrangement of such mushroom-like EBG structures was not limited by any interconnecting microstrip lines. Four columns of EBGs shifted inwards to antenna edges by 0.3mm (0.06λo) or a gap of its design around the patch from the left and right sides. Different configurations were also examined in order to get the better improvement in antenna performance. The final design of this mushroom-like shifted periodic structure shows an effective increase in the directivity by 77%, gain by 108%, bandwidth by 29% and the efficiency by 20% for the antenna. This structure has diversified application possibility for wireless and satellite communications.